Pomen tehnologije in religije v kontekstu teistične evolucije Teilharda de Chardina - Pohar, Borut (Bogoslovni vestnik, 2023)
One of the first pioneers to try to reconcile the Catholic doctrine of creation, salvation and redemption with the idea of evolution was the French Jesuit Pierre Teilhard de Chardin. He believed that humanity has an important role to play in the further development of the universe, since human consciousness or thought represents the highest stage of the evolution of the universe. This evolution was to be completed by reaching the Omega Point, which draws the universe and humanity towards the perfect complex interconnectedness. This is a distinctly teleological, finalistic view of the evolution of the universe and of life in it, and the Omega Point is associated with Christ, as depicted in some of the writings of the New Testament. In this paper, two hypotheses are put forward on the basis of Teilhard’s philosophy and proved by scientific facts. The first is that in the evolution of nature, that is, of the material universe (cosmogenesis), of life (abiogenesis) and of thought or spirit (noogenesis), we can see the solution of the original theological problem, namely, the evil of disconnectedness, by means of the integration of simple parts into a complex whole. The second hypothesis argues that modern technology is one of the phenomena of evolution, specifically of noogenesis, because by facilitating the flow of information and transdisciplinary learning, research and collaboration, it can foster the interweaving of simple thoughts and thinking persons into a complex whole. This is not to overlook the pressing problem where technology is not only connective but also disruptive, not because it is inherently bad, but because of the unhealthy spirit of a society that is immature to the new gains of humanity due to a weak moral consciousness. In this article we suggest that guidelines for the ethical use of technology should also be developed from the perspective of the Omega Point, namely from the ultimate full complex interconnectedness of creation, and that the motivation for following them should be found in the meaningful and realizes identity of the persons who use them.
Keywords: complexity; evolucija; evolution; interconnectedness; interweaving; kompleksnost; poklicna etika; povezanost; prepletanje; proces; process; professional ethics; religija; religion; science; technology; tehnologija; Teilhard de Chardin, Pierre; znanost